Packaging strategy in competitive pharmaceutical markets : convention or dose-customized blister packs? - Wei, Kuo-Hau (Universiti Malaysia Sarawak (UNIMAS), 2003)
The main objectives of this research are to find out whether by customizing design of blister packs for improving compliance, the dose-customized blister packs would be the preferred choice of the healthcare professionals for dispensing and to find out whether Y.S.P. should adopt the concept of dose-customized blister packs